American school reform : what works, what fails, and why - McDonald, Joseph P., 1974- (Chicago ; London : The University of Chicago Press, 2014)
Dissecting twenty years of educational politics in our nation s largest cities, "American School Reform" offers one of the clearest assessments of school reform as it has played out in our recent history. Joseph P. McDonald and his colleagues evaluate the half-billion-dollar Annenberg Challengelaunched in 1994alongside other large-scale reform efforts that have taken place in New York, Chicago, Philadelphia, and the San Francisco Bay Area. They look deeply at what school reform really is, how it works, how it fails, and what differences it can make nonetheless. McDonald and his colleagues lay out several interrelated ideas in what they call a theory of action space. Frequently education policy gets so ambitious that implementing it becomes a near impossibility. Action space, however, is what takes shape when talented educators, leaders, and reformers guide the social capital of civic leaders and the financial capital of governments, foundations, corporations, and other backers toward true results. Exploring these extraordinary collaborations through their lifespans and their influences on future efforts, the authors provide political hopethat reform efforts can work, and that our schools can be made better.
The theory of action space -- Action space in Chicago and New York -- Action space in context: Philadelphia and the Bay area -- Learning from collapse in Philadelphia and Chicago -- Learning from connections in New York -- Implications for practice.
Includes bibliographical references (pages 163-186) and index.
Keywords: Educational change -- Illinois -- Chicago; Cambio educativo -- Estados Unidos; Educational change -- New York (State) -- New York; Educational change -- Pennsylvania -- Philadelphia; Educational change -- California -- San Francisco Bay Area